Types and Factors Associated With Online Health Information Seeking Among College Men in Latino Fraternities: A Qualitative Study. (November 2017) - Chavarria, Enmanuel Antonio; Chaney, Elizabeth Hensleigh; Stellefson, Michael Leland; Chaney, J. Don; Chavarria, Nikita; Dodd, Virginia Jones
Despite the fact that a large percentage of Americans go online to seek health information, literature pertaining to online health information (OHI) seeking among college men in Latino fraternities (CMLF) has been nonexistent. Thus, the purpose of this study was to (a) identify the types of OHI that CMLF seek and (b) to determine the factors motivating OHI seeking among CMLF. Four 1- to 1.5-hour focus groups were conducted in two public universities in Florida with 41 college-aged Latino males in an established Latino fraternity. E-mails were used to recruit fraternity members. Qualitative analysis of the focus group transcripts identified that CMLF search for a variety of OHI types including searches on symptoms, diagnoses, weight loss, and treatments for conditions or diseases among other types of OHI. Factors motivating OHI seeking included informational needs of others and concerns for others, worries due to lack of health insurance, preoccupations with health condition, concerns over physical appearance, and clarification through social media. CMLF may be elicited to serve as information conduits to increase access to health information on chronic diseases for older non-English-speaking Latino adults. Lack of health insurance along with other factors in this segment of the population have led to self-diagnosis and self-treatment of illness. Thus, empirical research and health promotion on the potential risks due to self-diagnosing and self-treatment of illness is warranted among CMLF.